2020
DOI: 10.1186/s40168-020-00801-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plants on the diversity and activity of methylotrophs in soil

Abstract: Background: Methanol is the second most abundant volatile organic compound in the atmosphere, with the majority produced as a metabolic by-product during plant growth. There is a large disparity between the estimated amount of methanol produced by plants and the amount which escapes to the atmosphere. This may be due to utilisation of methanol by plant-associated methanol-consuming bacteria (methylotrophs). The use of molecular probes has previously been effective in characterising the diversity of methylotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 92 publications
(131 reference statements)
12
45
1
Order By: Relevance
“…Pseudomonadaceae were identified as potential root exudate utilisers within the rhizosphere, in agreement with previous studies [42,66]. These bacterial groups were also consistently enriched in the rhizosphere or endosphere, regardless of soil type.…”
Section: Burkholderiaceae-family Taxa (Comamonadaceae and Oxalobactersupporting
confidence: 90%
“…Pseudomonadaceae were identified as potential root exudate utilisers within the rhizosphere, in agreement with previous studies [42,66]. These bacterial groups were also consistently enriched in the rhizosphere or endosphere, regardless of soil type.…”
Section: Burkholderiaceae-family Taxa (Comamonadaceae and Oxalobactersupporting
confidence: 90%
“…The N 2 -fixing activity of diazotrophic methanotrophs under N-rich conditions needs to be studied in more detail in the future. Moreover, methanotrophic N 2 -fixing bacteria (Methylosinus and Methylocystis) in the roots, and other N 2 -fixing bacteria, such as Bradyrhizobium, Rhizobium, and Methyloceanibacter, which are frequently detected as methanol-oxidizing bacteria using metaproteomics or functional gene mxaF/xoxF sequencing analysis (Bao et al, 2014a;Macey et al, 2020), may utilize the methanol produced via the methane oxidation process to perform N 2 fixation. However, this relationship changes with nitrogen supplementation because the N 2 -fixing capacity of Bradyrhizobium and Rhizobium is inhibited by nitrogen (Kumar et al, 2018), while that of diazotrophic methanotrophs is more stable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, eCO 2 significantly increases the total organic carbon content of rice root exudates (Bhattacharyya et al, 2013), which may influence the diversity and activity of rhizospheric and root-associated C1 bacteria. Macey et al (2020) reported that methanol-utilizing methylotrophs were widely distributed in land plant-associated soil because they use the methanol produced as a metabolic byproduct during plant growth. Thus, C1-cycling bacteria in the root zones of both terrestrial plants and aquatic plants are important for the balance of carbon and nitrogen cycling and can increase benefits for plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria in this family have been found in soils with high heavy metal content and include microbes critical for heavy metal attenuation and immobilization [73,74]. Members of Methylophilaceae also form tight symbioses with plants [75][76][77] and are even known to promote seed germination and plant growth [76]. This family may include important taxa for serpentine-adapted species, with a decrease in relative abundance driving negative effects through reduced heavy metal attenuation and plant growth.…”
Section: Discussionmentioning
confidence: 99%